2014
DOI: 10.1016/j.bbabio.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of constitutive expression of bacterial phytoene desaturase CRTI on photosynthetic electron transport in Arabidopsis thaliana

Abstract: The constitutive expression of the bacterial carotene desaturase (CRTI) in Arabidopsis thaliana leads to increased susceptibility of leaves to light-induced damage. Changes in the photosynthetic electron transport chain rather than alterations of the carotenoid composition in the antenna were responsible for the increased photoinhibition. A much higher level of superoxide/hydrogen peroxide was generated in the light in thylakoid membranes from the CRTI expressing lines than in wild-type while the level of sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Constitutive expression of CrtI in the leaves of transgenic wheat lines OEI and OEIB was consistent with results from transgenic tobacco and Arabidopsis, resulting in a significant decrease in lutein content in parallel with a slight reduction in chlorophyll content (Misawa et al , 1993; Galzerano et al , 2014). It has been documented that the accumulation of phytoene leads to the metabolic feedback regulation of PSY and its upstream geranylgeranyl pyrophosphate synthase in the carotenoid biosynthetic pathway (Cazzonelli and Pogson, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Constitutive expression of CrtI in the leaves of transgenic wheat lines OEI and OEIB was consistent with results from transgenic tobacco and Arabidopsis, resulting in a significant decrease in lutein content in parallel with a slight reduction in chlorophyll content (Misawa et al , 1993; Galzerano et al , 2014). It has been documented that the accumulation of phytoene leads to the metabolic feedback regulation of PSY and its upstream geranylgeranyl pyrophosphate synthase in the carotenoid biosynthetic pathway (Cazzonelli and Pogson, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…In this regard, Ahmad et al (2012) have reported a dramatic decline in the NDH activity in tobacco expressing PTOX from green algae (Cr-PTOX1). Furthermore, PTOX may efficiently compete with CEF for the plastoquinol (PQH 2 ) in the CRTI-expressing (carotene desaturase) lines (Galzerano et al, 2014). Joët et al (2002) also showed a decrease in the NDH-dependent CEF flux in tobacco transgenic lines expressing PTOX from Arabidopsis.…”
Section: Ptox and Ndh-mediated Cyclic Electron Transfermentioning
confidence: 99%
“…There are, however, conditions where PTOX seems unable to take up this mechanistic challenge. When overexpressed in tobacco lines or when having to cohabit in the thylakoid membrane with a heterologously expressed bacterial phytoene desaturase, PTOX is a strong ROS producer (41,50). Interestingly, in vitro studies recently provided further insights into the balance between the antioxidant (oxygen-reducing) and prooxidant (ROS-producing) activity of PTOX.…”
Section: Functional Properties Of Ptox As Deduced From In Vitro and Hmentioning
confidence: 99%
“…Because it is a poor competitor of the photosynthetic mainstream, PTOX is unlikely to be a major player in photoprotection, at least under constant and saturating light conditions. Another feature of PTOX that argues against the safety valve function is its contribution to ROS production (33,41,50,167), which may damage the photosynthetic apparatus. However, according to Li et al (84), PTOX may consume up to 10% of photochemically produced oxygen via the astaxanthin biosynthesis pathway, which would lower the oxygen partial pressure in the cell and consequently decrease ROS production (84).…”
Section: The Electron Sink Hypothesismentioning
confidence: 99%